2020
DOI: 10.3389/fcell.2020.00676
|View full text |Cite
|
Sign up to set email alerts
|

Host-Defense Peptides Caerin 1.1 and 1.9 Stimulate TNF-Alpha-Dependent Apoptotic Signals in Human Cervical Cancer HeLa Cells

Abstract: Caerin 1.1/1.9 Induce HeLa Cell Apoptosis implies the likelihood of recruiting more T cells to the cell growth environment post the treatment and more sensitive to T cell mediated killing of HeLa cells. Our results indicate that caerin 1.1 and 1.9 mediate apoptotic signals of HeLa cells and may subsequently enhances adaptive T cell immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…Total protein was extracted by a previously described method [ 16 ]. Briefly, the protein concentration of F1-treated CAL-62 cells was detected by the BCA method (Thermo Scientific, USA), and the extracts containing equal amounts of proteins (20 μg) were electrophoresed in the desired concentration of polyacrylamide gel according to the size of the target protein and then transferred to a PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Total protein was extracted by a previously described method [ 16 ]. Briefly, the protein concentration of F1-treated CAL-62 cells was detected by the BCA method (Thermo Scientific, USA), and the extracts containing equal amounts of proteins (20 μg) were electrophoresed in the desired concentration of polyacrylamide gel according to the size of the target protein and then transferred to a PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Many of these peptides, including caerin peptides, have antiviral, antitumor, antimicrobial, and/or neuropeptide-type activities (7)(8)(9)(10). Caerin 1.1 has an anti-cancer effect against a number of human cancer cell lines, including leukaemia, lung, colon, CNS, melanoma, ovarian, renal, prostate, and breast cancers (8,11).…”
Section: Introductionmentioning
confidence: 99%
“…Caerin 1.1 and 1.9 inhibit HIV-infected T cells within minutes post-exposure at concentrations non-toxic to T cells and inhibit the transfer of HIV from dendritic cells (DCs) to T cells with limited toxicity (10,16). Recently, it has been shown that Caerin 1.1 and Caerin 1.9 peptides have additive effects against human papillomavirus transformed tumour cells and increase the efficacy of a therapeutic vaccine against HPV related diseases (9,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most common malignancies in women ( Cisse et al, 2019 ; Feng et al, 2019 ; Vliet-Gregg et al, 2019 ; Wang et al, 2020b ), leading to major health problems for high morbidity and mortality ( Li et al, 2019 ; Ni et al, 2020 ; Wang et al, 2020d ; Wu et al, 2020a ). Cervical cancer is mainly caused by the human papilloma virus infection ( Ding et al, 2019 ; Young et al, 2019 ; Cerasuolo et al, 2020 ), and is one of the most common gynecological malignancies, and its incidence rate ranks second among female malignancies in developing countries, and is behind breast cancer ( Cisse et al, 2019 ; Li et al, 2019 ; Ni et al, 2020 ; Wang et al, 2020d ; Wu et al, 2020a ), and its mortality rate ranks third that is behind breast cancer and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most common malignancies in women ( Cisse et al, 2019 ; Feng et al, 2019 ; Vliet-Gregg et al, 2019 ; Wang et al, 2020b ), leading to major health problems for high morbidity and mortality ( Li et al, 2019 ; Ni et al, 2020 ; Wang et al, 2020d ; Wu et al, 2020a ). Cervical cancer is mainly caused by the human papilloma virus infection ( Ding et al, 2019 ; Young et al, 2019 ; Cerasuolo et al, 2020 ), and is one of the most common gynecological malignancies, and its incidence rate ranks second among female malignancies in developing countries, and is behind breast cancer ( Cisse et al, 2019 ; Li et al, 2019 ; Ni et al, 2020 ; Wang et al, 2020d ; Wu et al, 2020a ), and its mortality rate ranks third that is behind breast cancer and lung cancer. At present, surgery, radiotherapy, and chemotherapy have a better effect on early cervical cancer ( Hu et al, 2019 ; Harkenrider et al, 2020 ; Rotman et al, 2020 ; Wang et al, 2020a ), which its 5-year survival rates could reach 91.5%, but its efficacy on advanced and metastatic cervical cancers is very limited with its 5-year survival rate is only 17.3% ( Wang et al, 2019 ; Chen et al, 2020 ; Du et al, 2020 ; Zhang et al, 2020b ), meanwhile, the survival rate of recurrent cervical cancer is lower ( Jayamohan et al, 2019 ; Wei et al, 2019 ; Yuan et al, 2019 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%